Ciprofloxacin HCl and quercetin functionalized electrospun nanofiber membrane : fabrication and its evaluation in full thickness wound healing - Ajmal, Gufran (2020)
Microbial infection and oxidative damage of the fibroblast often results in prolonged and incomplete wound healing. Therefore, there is an increasing demand for a scaffold being effective to prevent any possible infection and neutralize excessively released free radicals. Herein, we designed a PCL-based nanofiber loaded with ciprofloxacin hydrochloride (CHL) and quercetin. Developed nanofiber showed the formation of smooth and continuous nanofiber with 101.59 ± 29.18 nm average diameter and entrapping the drugs in amorphous form without any possible physico-chemical interaction between drugs and excipient. High entrapment efficiency (CHL: 92.04% and Que: 94.32%) and prolonged in-vitro release (for 7 days) demonstrated the capability of scaffold to suppress any probable infection and oxidative damage, which was further confirmed by in-vitro antibacterial and antioxidant activity. The biocompatibility of scaffold for direct application to wound site was evaluated through hemocompatibility and cytocompatibility assay. The wound healing efficacies of nanofiber were assessed using full thickness wound model in rats, which displayed accelerated wound healing with complete re-epithelialization and improved collagen deposition within 16 days. In-vivo wound healing finding was further corroborated by SOD, catalase, and hydroxyproline assay. The current study validates the application of ciprofloxacin HCl and quercetin functionalized nanofiber as a potential wound dressing material.